The Debugging Mind-Set. - O'DELL, DEVON H. (Communications of the ACM, 2017)
The article discusses the psychology of software debugging by computer programmers in relation to learning strategies and problem-solving. Topics include self-theories of intelligence and learning, the thought of learning theorist Carol Dweck, and the adoption of self-theories of malleable intelligence by organizations. Strategies for debugging are addressed in relation to the formation of hypotheses.